If You See Me, Don't Say Hi - Patel, Neel (Flatiron Books, 2018)
In eleven sharp, surprising stories, Neel Patel gives voice to our most deeply held stereotypes and then slowly undermines them. His characters, almost all of who are first-generation Indian Americans, subvert our expectations that they will sit quietly by. We meet two brothers caught in an elaborate web of envy and loathing; a young gay man who becomes involved with an older man whose secret he could never guess; three women who almost gleefully throw off the pleasant agreeability society asks of them; and, in the final pair of linked stories, a young couple struggling against the devastating force of community gossip.